2017
DOI: 10.1016/j.jstrokecerebrovasdis.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensity Associations with Cerebral Blood Flow in Elderly Subjects Stratified by Cerebrovascular Risk

Abstract: Goal Add clarity to the relationship between deep and periventricular brain white matter hyperintensities, cerebral blood flow and cerebrovascular risk in older persons. Methods Deep and periventricular WMH and regional grey and white matter blood flow from arterial spin labeling were quantified from magnetic resonance imaging scans of 26 cognitively normal elder subjects stratified by cerebrovascular disease risk. FLAIR images were acquired using a high-resolution 3D sequence that reduced partial volume eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 43 publications
(32 reference statements)
2
60
0
1
Order By: Relevance
“…Compared to manual results, computed semi‐automatically measured brain volume showed high agreement with an R 2 of 0.93 . This semi‐automated technique was widely used to measure WMH volume in many previous studies .…”
Section: Methodsmentioning
confidence: 71%
“…Compared to manual results, computed semi‐automatically measured brain volume showed high agreement with an R 2 of 0.93 . This semi‐automated technique was widely used to measure WMH volume in many previous studies .…”
Section: Methodsmentioning
confidence: 71%
“…They found two important markers: the first was that deep WMH is associated with decreased regional cortical blood flow, and the second that blood flow in WM shows a greater reduction in the periventricular than in deep WMH areas. The strongest and most consistent risk factors that showed the clearest association with WMH were age, hypertension, hypercholesterolemia, diabetes and smoke [34].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the only current evidence for ASL‐derived perfusion changes in relation to the chronic use of cholesterol medication points, not to decreases, but rather to increases in regional CBF (not in the auditory cortex) in persons at risk for AD (Carlsson et al, ). Moreover, recent work reported that periventricular, but not deep, white matter lesions were associated with regional cortical CBF reductions in elderly subjects at risk for cerebrovascular diseases (Bahrani et al, ).…”
Section: Discussionmentioning
confidence: 99%